Experimental Determination of the Fluorescence Quantum Yield of Semiconductor Nanocrystals - Agnès Maître (Materials, 2011)
Many studies have considered the luminescence of colloidal II–VI nanocrystals, both in solution at a collective scale and at an individual scale by confocal microscopy. The quantum yield is an important figure of merit for the optical quality of a fluorophore. We detail here a simple method to determine the quantum yield of nanocrystals in solution as a function of the absorption. For this purpose, we choose rhodamine 101 as a reference dye to measure the nanocrystal fluorescence quantum yield. The influence of the concentration on quantum yield is therefore studied for both the reference and the solutions of nanocrystals and is found to be critical for the acuity of the method. Different types of nanocrystals are studied to illustrate different quantum yield evolutions with the concentration.